A Cooperative Photoactive Class-I Hybrid Polyoxometalate With Benzothiadiazole–Imidazolium Cations - Kibler, Alexander J.; Souza, Virginia S.; Fernandes, Jesum Alves; Lewis, William; Argent, Stephen P.; Dupont, Jairton; Newton, Graham N. (Frontiers in Chemistry, 2021)
An organic-inorganic hybrid species based on the Wells-Dawson polyoxotungstate [P2W18O62]6- and novel fluorescent benzothiadiazole-imidazolium cations, [BTD-4,7-ImH]2+, has been synthesized. X-ray crystallographic analysis shows that the inorganic and organic components form a hydrogen-bonded superstructure and the cations are revealed to be non-equivalent with varying degrees of rotation between the BTD and imidazolium rings due to competition between weak intra- and intermolecular interactions. The UV-vis diffuse reflectance spectra indicate that the hybrid has a band gap of 3.13 eV, while the solid-state fluorescence properties of the cation are quenched in the hybrid material, suggesting the existence of electron transfer between the inorganic and organic components. The HOMO and LUMO energies of the POM and BTD-4,7-ImH precursors, estimated through UV-vis absorption spectroscopy and cyclic voltammetry, indicate that electron transfer from the BTD cations to the POM may occur in the excited state.